2015
DOI: 10.1007/s11845-015-1339-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lead and essential elements in whole blood during pregnancy: a cross-sectional study

Abstract: The importance of Cu and Mg deficiency and supplementation is well realized, but, Zn/Ca deficiency and Pb exposure is still exist; the overall deficiency of pregnant women was not so optimistic. During pregnancy, the established reference values will provide an important guidance for the reasonable supplementation of essential elements and surveillance of lead overexposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…The median concentration of lead in maternal erythrocytes was 94 μg/kg, corresponding to 4 μg/dl in whole blood, assuming 99% of blood lead in the erythrocytes, 41% hematocrit, and an erythrocyte density factor of 1.06 kg/l. These levels are similar to those observed in pregnant women in China and Mexico [ 40 , 41 ] and higher than those measured in pregnant women in Canada and Germany [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 86%
“…The median concentration of lead in maternal erythrocytes was 94 μg/kg, corresponding to 4 μg/dl in whole blood, assuming 99% of blood lead in the erythrocytes, 41% hematocrit, and an erythrocyte density factor of 1.06 kg/l. These levels are similar to those observed in pregnant women in China and Mexico [ 40 , 41 ] and higher than those measured in pregnant women in Canada and Germany [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, Ugwuja et al [ 5 ] found a negative correlation between the plasma Cu level and the newborn’s head circumference. In this study, we observed a positive association between the Cu level and the MBM/NBM ratio, which may be related to the increase in the mother’s Cu content during pregnancy [ 8 , 20 , 21 , 23 ].…”
Section: Discussionmentioning
confidence: 87%
“…The average Mg concentration in the serum was slightly lower than in non-pregnant women [19, 22]. It was confirmed that blood levels of Mg in pregnant women decreases as the pregnancy progresses [6, 15, 23]. Mg plays an important role in development during pregnancy and is utilized both for building the fetal body and metabolism in the fetus.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Zhang et al and Liu et al reported that the level of Ca in the first trimester is lower than that in the third trimester, possibly because the foetal demand for Ca increases compared with that in early pregnancy [20,21]. Growing evidence has shown that the prevalence of maternal Ca supplementation before and during pregnancy in China is lower than that in developed countries [22][23][24].…”
Section: Discussionmentioning
confidence: 99%